Perbedaan IFRS, U.S. GAAP, dan PSAK: Investement Property - Nunik L.D. (Universitas Kristen Maranatha, 2010)
International accounting standards convergence which has been done through adopting IFRS completely by DSAK is IAS 40 Investment Property. Based on these adopting, there will be differentiation between IFRS, U.S. GAAP and PSAK. But for PSAK valid in January 1st 2008 (SAK in July 1st 2009), there are no differentiation with IFRS because PSAK adopts IFRS completely, but between IFRS, PSAK and U.S. GAAP have differentiation. This paper will only discuss about the differentiation between IFRS, U.S. GAAP and PSAK in investment property, especially related to the differentiation of IFRS, U.S. GAAP and PSAK in presentation, recognition, measurement and disclosure. Keyword: IFRS, U.S. GAAP, PSAK, Investment Property.